An improved method for whole-mount in situ hybridization in regenerating tails of Xenopus laevis tadpoles - Shitikov, A. D.; Parshina, E. A.; Zaraisky, A. G.; Tereshina, M. B. (Frontiers in Cell and Developmental Biology, 2024)
Whole-mount in situ hybridization (WISH) is a widely used method that supports the concept of “seeing is believing” by enabling the visualization of gene expression patterns in whole-mount multicellular samples or sections. This technique is essential in the study of epimorphic regeneration in cold-blooded vertebrates, where complex three-dimensional organs such as tails, limbs, and eyes are completely restored after loss. The tadpoles of the frog X. laevis serve as a convenient model for studying regeneration, as they can regenerate their tails within a week after amputation. Modern high-throughput sequencing methods have identified various cell populations involved in the regeneration process and determined the repertoire of genes activated during this time. Specifically, a population of reparative myeloid cells expressing mmp9 as a marker gene has been shown to be crucial for the initial stages of tail regeneration in X. laevis tadpoles. The validation of these data and further examination using WISH offers the advantage of providing detailed information on the spatial and temporal dynamics of target gene expression levels. However, detecting mRNA by WISH can be challenging when mRNA levels are very low, transcripts are localized in hard-to-access areas, or tissue samples are prone to background staining, as is the case with X. laevis regenerating tail samples. Here, we describe additional treatments for regenerating tail samples that minimize background staining and enhance the visualization of cells containing target RNA through in situ hybridization. Using an optimized WISH protocol on X. laevis tadpole tail regenerates, we obtained novel data on the mmp9 expression pattern during the first day post-amputation at the regeneration-competent stage 40 and the regeneration-incompetent stage 47 (refractory period). The significant differences in the expression patterns indicate that mmp9 activity is positively correlated with regeneration competence.